An overview of Study on Mobile Banking in Bangladesh: Area of Rangpur Division - Md. Akash; Md. Jahidul Islam Jahid; Md Ahsan Habib (Financial Markets, Institutions and Risks)
Several bank in Bangladesh offer their financial services using mobile technology. Mobile transactions are simple and economical for clients. Mobile banking is performing of the finance of the finance related functions on a mobile device such as smartphone or tablet. This paper provides a picture of how mobile banking now operates and what it could look like in the future. The future of the banking industry will get brighter every day as a result of the study's conclusion that clients are happy with the services provided by the new banking system. This article will significantly benefit Bangladeshi banks by improving service delivery and raising consumer awareness of available options.